MEMBANGUN DESA AGROEKOLOGIS MELALUI KKN TEMATIK DI DESA BANGSAL KECAMATAN PAMPANGAN KABUPATEN OGAN KOMERING ILIR - Erise Anggraini (Fakultas Pertanian_Universitas Tidar, 2023)
Bangsal Village, Pampangan District, and Ogan Komering Ilir Regency have rich natural resource potential; however, most of the people in the village have low incomes. Thematic KKN activities are designed to increase the acceleration and effectiveness of the Bangsal Village development program, which is characterized by improving the quality of community life in harmony with the landscape by involving students and their accompanying lecturers through thematic education programs. The results of the thematic KKN activities have instilled public awareness, especially among millennials. In this case, Ibnul Fallah Islamic Boarding School students actively participated in improving welfare by enhancing knowledge in agriculture, financial management, and village websites. Programs that the community has successfully adopted include the cultivation of hydroponic vegetables and soil media, increasing maggots, activating village websites, and managing simple finances. Meanwhile, a less successful program was applying urea mineral molasses block supplementation for buffalo fattening because buffaloes did not like the food yet.